A Rare Case of Aortic Valve Thrombosis in Patient with Idiopathic Hypereosinophilic Syndrome. (8th September 2015) - Grolla, Elisabetta; Dalla Vestra, Michele; Bonanni, Luca; Cutolo, Ada; Rigo, Fausto
Abstract : Idiopathic hypereosinophilic syndrome (HES) is characterized by persistent eosinophilia and eosinophil-mediated organ-system damage. Cardiac thrombosis and thromboembolic complications represent common causes of morbidity and mortality and usually involve cardiac ventricles or mitral and prosthetic valves, while the involvement of the aortic valve is extremely rare in HES. Here we report peculiar multimodality images of an atypical case of extended thrombosis of the aortic valve, complicated by myocardial ischemia and asymptomatic cerebral ischemia, likely due to thrombus embolization, occurring in a 48-year-old man with HES. Prompt anticoagulant and steroid therapy lead to rapid and complete resolution of the thrombotic lesions, allowing preserving the native valve and preventing further embolic events.